Treatment with bortezomib‐based regimens improves overall response and predicts for survival in patients with primary or secondary plasma cell leukemia: Analysis of the Greek myeloma study group. Issue 2 (21st November 2013) - Katodritou, Eirini; Terpos, Evangelos; Kelaidi, Charikleia; Kotsopoulou, Maria; Delimpasi, Sossana; Kyrtsonis, Marie‐Christine; Symeonidis, Argiris; Giannakoulas, Nikos; Stefanoudaki, Aikaterini; Christoulas, Dimitrios; Chatziaggelidou, Christina; Gastari, Vassiliki; et al.
<x xml:space="preserve">Abstract</x> Plasma cell leukemia (PCL) is a rare and aggressive plasma cell disorder, with poor outcome. Bortezomib‐based regimens (BBR) are highly effective in myeloma, but there is limited information about their efficacy and safety in PCL. Thus, we retrospectively collected data from 42 consecutive PCL patients (25 with primary PCL‐pPCL and 17 with secondary PCL‐sPCL) to explore the role of BBR in this entity. BBR were administered in 29 of 42 patients, while 6 of 25 patients with pPCL underwent autologous transplantation. Objective response (≥partial response) was significantly higher in patients treated with BBR versus conventional therapies (69% vs. 30.8%, P = 0.04); 27.5% of patients treated with BBR achieved at least very good partial response (vgPR). The highest ORR was observed in pPCL patients treated with BBR (88.9%; ≥vgPR: 33.3%). In BBR‐group, grade 3 of 4 hematological, neurological and renal toxicity and neutropenic infections were observed in 41.4%, 7%, 3.4%, and 31%, respectively. With a median follow‐up of 51 months, median overall survival (OS) for patients treated with BBR versus conventional therapies was 13 versus 2 months (P < 0.007). Median OS of patients with pPCL and sPCL treated with BBR was 18 and 7 months, respectively (P < 0.001). In the multivariate analysis normal PLTs, treatment with BBR and high quality response were the only powerful predictors for survival. Our study carrying the longest reported median follow‐up, demonstrated that treatment of PCL with BBR induces high response rates and prolongs survival over conventional therapies, regardless of additional autologous transplantation rescue or established high risk features, with manageable toxicity. Am. J. Hematol. 89:145–150, 2014. © 2013 Wiley Periodicals, Inc.